Fresh Flour As a Symbol Hope Perpetuate Marriage: Cultural Practices of Marriage in Riau Islands - Beddu, Muhammad Juni; Azhari, Muhammad Iqbal; Addieningrum, Fithri Mehdini; Ruhmah , Andi Amma; Husain, Muhammad Zakir; Daud, Normadiah (Al-Risalah, 2024)
Abstract: This research examines the role of plain flour in religious, cultural, social, and marriage perspectives in the Riau Islands community. Plain flour is a practice that is closely related to wedding ceremonies in the Riau Islands region. This research method uses a qualitative approach with the data collected through literature related to Tepung Tawar in Religious, Cultural, Social, and Marital Perspectives in the Riau Islands Community. This research also uses a descriptive method, namely explaining. This research uses a historical and contextual approach. The analytical method used is content analysis, namely digging deeper into the importance of plain flour from a religious, cultural, social, and marriage perspective in the Riau Islands community by reviewing various literature. The research results show that plain flour has essential meaning and function in the context of religion, culture, society, and marriage in the Riau Islands community. From a religious perspective, plain flour is used as a form of offering to the gods and goddesses and to cleanse negative energy that may exist in marital relationships. This practice is also considered an attempt to invoke blessings and good luck in marriage.